Anonymous

How Do You Solve 4+3x-6=3x+2-x?

1 Answers

michael finnegan Profile
Start by simplifying the question:

4 + 3x - 6 could be rewritten as 3x + 4 - 6 , or 3x - 2

3x + 2 - x could be rewritten as 3x - x + 2 , or 2x + 2

so then, 3x - 2 = 2x + 2. Subtract 2x from both sides:

3x - 2x - 2 = 2x - 2x +2, or x - 2 = 2

x = 4
thanked the writer.
michael finnegan
michael finnegan commented
I guess it would've been easier to subtract 3x from both sides, then you'd have
4 - 6 = 2 - x , or -2 = 2 - x. Subtract 2 from both sides: -4 = -x , or 4 = x

Answer Question

Anonymous